Perspectives in Cancer Prevention-Translational Cancer Research - R. Sudhakaran, Perumana; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
Being a complex disease that affects millions of people world over, cancer research has assumed great significance. Translational cancer research transforms scientific discoveries in the laboratory or population studies into clinical application to reduce incidence of cancer , morbidity and mortality. It is becoming increasingly evident that cancer is a preventable disease. The IVth International Symposium on Translational Cancer Research held in Udaipur, India in December 2011, discussed various aspects of the biological processes in cancer cells and approaches to cancer prevention. A few contributions from this meeting are presented in this book, providing an in depth analysis of data on cancer prevention and therapeutics. These contributions are either critical reviews or research reports. The topics discussed include evidence-based nutritional recommendations for cancer patients and survivors, risk factors such as stress, enrichment of tumour stem cells by anticancer drug treatment contributing to tumour recurrence and the mechanism of anticancer effects of various natural products. Chemosensitizing effect of curcumin, anti-cancer effect of products from neem, action of sulforaphane and cytotoxic effect of a number of novel synthetic coordination complexes of trace metals have been discussed. Novel molecular targets of angiogenesis and molecular basis of the gender bias to thyroid cancer have also been discussed . This book provides useful information on translational cancer research to clinicians and biomedical scientists.
1.Nutrition in Cancer: Evidence Based Nutrition Recommendations in Cancer Patients and Survivors -- 2.Tumor Stem Cell Enrichment by Anticancer Drugs: A Potential Mechanism of Tumor Recurrence -- 3. Curcumin: A potent candidate to be evaluated as a chemosensitizer in paclitaxel chemotherapy against cervical cancer -- 4. Azadirachta indica (Neem) and Neem Limonoids as Anticancer Agents: Molecular Mechanisms and Targets -- 5. In vitro studies on the antioxidant/antigenotoxic potential of aqueous fraction from Anthocephalus cadamba bark -- 6. Possible involvement of Signal Transducer and Activator of Transcription-3 (STAT3) Signaling Pathway in the Initiation and Progression of Hepatocellular Carcinoma -- 7. Simple Sequence Repeats In 5$1 (Band 3$1 (Bflanking sequences of Cell Cycle Genes -- 8.Mechanisms of Chemopreventive Activity of Sulforaphane -- 9. Reciprocal relationship between VE-cadherin and Matrixmetalloproteinase expression in Endothelial cells and its Implications to Angiogenesis -- 10. Androgen receptor expression in human thyroid cancer tissues: a potential mechanism underlying the gender bias in the incidence of thyroid cancers -- 11.Novel co-ordination complexes of a few essential trace metals: Cytotoxic properties and lead identification for drug development for cancer -- 12.Why Gallbladder Cancer is common in Gangetic Belt? -- 13. Stress & Cancer Risk: The Possible Role of Work Stress.s
Keywords: Medicine; Cancer research; Oncology; Biomedicine; Cancer Research; Biomedicine general; Oncology; Electronic books